Application of the Movement Disorder Society prodromal criteria in healthy G2019S‐LRRK2 carriers. Issue 6 (30th March 2018) - Mirelman, Anat; Saunders‐Pullman, Rachel; Alcalay, Roy N.; Shustak, Shiran; Thaler, Avner; Gurevich, Tanya; Raymond, Deborah; Mejia‐Santana, Helen; Orbe Reilly, Martha; Ozelius, Laurie; Clark, Lorraine; Gana‐Weisz, Mali; et al.
ABSTRACT: Background: In 2015, the International Parkinson and Movement Disorder Society Task Force recommended research criteria for the estimation of prodromal PD. Objectives: We aimed to evaluate, for the first time, the criteria in first‐degree relatives of Ashkenazi Jewish G2019S‐ LRRK2 PD patients, who are considered a population at risk for developing PD, and assess the sensitivity and specificity of the criteria in identifying phenoconverters. Methods: Participants were evaluated longitudinally over a period of 5 years (average follow‐up: 49.2 ± 12.3 months). Likelihood ratios and probability estimations were calculated based on the International Parkinson and Movement Disorder Society Research Criteria for Prodromal Parkinson's Disease markers and examined for each assessment point. Results: One hundred twenty healthy carriers (49.53 ± 13.4 years; 54% female) and 111 healthy noncarriers (48.43 ± 15.79 years; 49% female) participated in this study. Probability scores were significantly higher in healthy carriers than healthy noncarriers ( P < 0.0001). Of the 20 participants (8.6%) who met criteria for probable prodromal PD at baseline, 17 were healthy carriers. Participants who reached the threshold were older ( P < 0.0001), had higher UPDRS‐III ( P < 0.001), lower cognitive function ( P = 0.001), and more nonmotor symptoms ( P < 0.0001), compared to those who did not. Ten participants were diagnosed with incident PD within 5 years from baseline resulting in a specificity of 91.82% (95% confidence interval: 86.69‐96.94), sensitivity of 80% (95% confidence interval: 55.21‐100), positive predictive value of 47.06% (95% confidence interval: 23.33‐70.79), and negative predictive value of 98.06% (95% confidence interval: 95.39‐100). All 10 phenoconvertors were G2019S‐ LRRK2 carriers. Conclusions: The results showed the utility of using the criteria and high sensitivity and specificity in identifying prodromal PD in this high‐risk unique cohort. These results may be valuable for future disease modification clinical trials. © 2018 International Parkinson and Movement Disorder Society